The integrated risk analysis and risk assessment method of information security - Казмирчук, Светлана Владимировна; Гололобов, Андрей Юрьевич (Ukrainian Information Security Research Journal, 2015)
One of the stages of information security management system construction is provided with the realization of risk analysis and risk assessment process. Often in the assessment process there are some situations when theexpert can’t always clearly assess the information securitythreat. To solve these tasks the known determined or fuzzy methods are applied. According to these methods the corresponding systems have been developed. Practically,in some cases, it is necessary to carry out a risk assessmentwith a combination of approaches of the expertsinterpretation judgments both regarding their capabilitiesto determine the meaning of received assessedparameters, and their uncertainty in the accuracy of priorities.The specified assessment possibilities are not integratedin the existing systems. To address a challenge andsimplify the risks assessment the integrated risk analysisand risk assessment method is provided, which, in contrastto the well-known, enables to operate simultaneously the clear and fuzzy sets with the ability to transform theterms of linguistic variables.